2018
DOI: 10.1021/acs.iecr.8b00109
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis of Spherical Al-SBA-16 Mesoporous Materials with Different Crystal Sizes and Its High Isomerization Performance for Hydrodesulfurization of Dibenzothiophene and 4,6-Dimethyldibenzothiophene

Abstract: Series Al-SBA-16 supports with different crystal sizes were fabricated by adding different inorganic salts to the synthesis system and used as the catalyst support for dibenzothiophene (DBT) and 4,6-dimethyldibenzothiophene (4,6-DMDBT) hydrodesulfurization (HDS). The supports and the corresponding catalysts were well analyzed in depth to investigate their structure−property relationship. NiMo/AS-Mn catalyst with the smallest crystal sizes, the largest BET surface areas, and the highest total acid and Bronsted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…In recent years, mesoporous materials with highly ordered pore structure, large pore volume and specific surface area have drawn increasing interests in the field of catalysis and exhibited advantageous performance in the removal of aromatic sulfide molecules. Different kinds of mesoporous materials have been applied as the supports of HDS catalysts, such as MCM (Kaluza et al 2019;Mendez et al 2017;Wang et al 2005), HMS (Vutolkina et al 2019;Palcheva et al 2016), SBA (Wang et al 2018;Thanh Tung and Qian 2018;Yuan et al 2014) and KIT (Meng et al 2020;Soni et al 2010) series. The results showed that such supports favored the formation of type II active phases with good dispersion which exhibited higher HDS activity than γ-Al 2 O 3 supported catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, mesoporous materials with highly ordered pore structure, large pore volume and specific surface area have drawn increasing interests in the field of catalysis and exhibited advantageous performance in the removal of aromatic sulfide molecules. Different kinds of mesoporous materials have been applied as the supports of HDS catalysts, such as MCM (Kaluza et al 2019;Mendez et al 2017;Wang et al 2005), HMS (Vutolkina et al 2019;Palcheva et al 2016), SBA (Wang et al 2018;Thanh Tung and Qian 2018;Yuan et al 2014) and KIT (Meng et al 2020;Soni et al 2010) series. The results showed that such supports favored the formation of type II active phases with good dispersion which exhibited higher HDS activity than γ-Al 2 O 3 supported catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers discovered that inorganic salts distinctly influenced the properties of mesoporous silica material containing the morphology, structure property, and so on. Newalkar et al prepared ordered SBA-15 silica sieve using varied amounts of sodium chloride, and they discovered that the contents of sodium chloride had distinct influences on the pore sizes, pore volumes, and surface areas . Zhong et al reported that the kinds of inorganic salts used could affect the ordered degrees of meso-/macroporous monolithic silica materials following the sequence of NaCl > NaNO 3 > Na 2 SO 4 , and the addition of inorganic salts could improve the condensation of silica species .…”
Section: Introductionmentioning
confidence: 99%
“…There are several ways to remove the sulfur compounds from crude oil and commercial fuels. HDS (Hydrodesulfurization) is the most popular desulfurization method that is widely used in the oil industries . However, HDS operates at the hard operational condition and is not economically feasible.…”
Section: Introductionmentioning
confidence: 99%